Technical efficiency and motivation of contract and non-contract farmers participation in Thailand’s sugarcane loading station - Krisdakorn, Wongwai (2023)
In the sugarcane industry in Thailand, the sugarcane loading stations emerge as pivotal entities that significantly contribute to the reduction of transportation costs for sugarcane farmers. These loading stations serve as the hub for sugarcane farmers, playing a vital role in the search of sustainable agriculture practices. The decision-making process of farmers in selecting sugarcane contracts with specific loading stations is a complex process, influenced by numerous factors encompassing interpersonal relationships, financial considerations, and social standing. Understanding the influential factors associated with the management system of loading stations is imperative for enhancing the productivity of sugarcane farmers. The main objective of this study was to examine the impacts of loading stations on sugarcane farmers and the factors that farmers to participate as contract farmers. The methodology of this involved surveying 500 sugarcane small farmers in north-eastern Thailand using a questionnaire. Data analysis techniques such as statistics (frequency, percentage), factor analysis, multiple regression analysis, and Stochastic Frontier method were employed. The research identified two types of farmers: contract farmers (coded as 1) and non-contract farmers (coded as 0). The study found that contract farmers exhibited higher motivation and tended to stay longer at sugarcane loading stations compared to non-contract farmers. The positive and significant effect of the dummy variable coefficient on motivation suggested that contract farmers were more inclined to continue their relationships with the loading stations. The technical efficiency of sugarcane production was analysed using the Cobb- Douglas Frontier 4.1 method. The total average efficiency of sugarcane farmers at transfer stations was 78.06 %. Contract farmers had the potential to improve efficiency by 0.22, while farmers without contracts had an average efficiency of 81.06 and could increase the efficiency by 0.19. Promoting sugarcane farming to meet production targets requires creating common goal awareness and fostering development. Sugar mill staff have been involved in sharing knowledge with sugarcane farmers, focusing on cultivation practices and benefits. The decision of farmers to stay in the sugarcane and sugar industry is influenced by factors such as financial considerations, loans, and support. Government agencies are urged to fulfil their duties by promoting cooperation and completing missions through a network. The proposal includes creating a system to track production and provide support, advocating for policies following regulations, and preventing disputes to assist sugarcane farmers effectively.